A Comparison of collateral sprouting of sensory and motor axons after end-to-side neurorrhaphy with and without the perineurial window - Haninec, Pavel; Kaiser, Radek; Dubový, Petr (Plastic and reconstructive surgery, 2012)
BACKGROUND: Many experimental studies have confirmed collateral sprouting of axons after end-to-side neurorrhaphy and its possible clinical application. There is still controversy about how the surgical method should be carried out. The aim of the present study was to quantitatively evaluate collateral sprouting of motor and sensory axons after end-to-side neurorrhaphy with and without the perineurial window. METHODS: End-to-side neurorrhaphy of the distal stump of transected musculocutaneous nerve with intact ulnar nerve with or without a perineurial window was performed in a rat model. Collateral sprouts were quantitatively evaluated by counting of motor and sensory neurons following their retrograde labeling by Fluoro-Ruby and Fluoro-Emerald applied to the ulnar and musculocutaneous nerves, respectively. RESULTS: Our results show that significantly more motor and sensory axons sent their collateral branches into the recipient nerve in the group with a perineurial window. Some axons were injured during preparation of the perineurial window; the injured axons reinnervated directly into the recipient nerve to contribute to results of functional reinnervation. CONCLUSION: The authors conclude that it is necessary to create a perineurial window when using end-to-side neurorrhaphy in clinical practice, especially in brachial plexus reconstruction.
Keywords: Animals; Motor Neurons; Musculocutaneous Nerve; Rats, Wistar; axony; Peripheral Nerves; anastomóza chirurgická; nervové receptory; Grooming; péče o zevnějšek u zvířat; Sensory Receptor Cells; Male; Ganglia, Spinal; nervus musculocutaneus; Anastomosis, Surgical; periferní nervy; motorické neurony; spinální ganglia; krysa rodu Rattus; Ulnar Nerve; zvířata; mužské pohlaví; Rats; nervus ulnaris; potkani Wistar; Axons